“Aqui em casa, com o tablet e videogame, eu sempre aprendo um montão de coisas” : atos de currículo brincantes nas práticas das culturas infantis com as tecnologias digitais - Oliveira, Bruna Santana de (2021)
In face of the advances of contemporary society, digital technologies are increasingly part of the interactions of social actors, highlighted, gradually, are the children who mirror their parents and begin to explore the virtual universe in an incipient way. These protagonisms in the networks enhance curriculum acts not experienced in the pedagogical practices of the school context, however, they are present in the scenarios of children's cultures as educational experiences in daily practices. In this sense, this research aims to understand the curriculum acts constructed in children's cultures with digital technologies. This study is based on the multireferential epistemology for a plural look at educational phenomena bricolated to the strategies of the participatory research methodology with children. To this end, this qualitative research is based on inspiration in the assumptions of ethnography for listening to the voices of the children themselves as authors of the experiences of children's cultures in the digital network. The devices used for the production of data were: field diary, interactive observation lasting four months in the private family space of two children aged three and five years and moments of play. The results point out the curricular authorship through games, therefore, the notion “acts of curricula playing with digital technologies” and three sub-notions emerged: transmedia narrative and connectivity in games; imaginary transposition between the real and the virtual, and, finally, learning strategies with digital technologies. In this way, the study showed that the aspects constructed from the performance of the little ones in digital cultures enhance the curriculum acts through games, also enriched the imagery production strategies and learning postures resulting from this contact.